2011
DOI: 10.1007/s00405-011-1702-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of sphenopalatine ganglion block for postoperative analgesia after functional endoscopic sinus surgery

Abstract: The aim of this study was to evaluate the analgesic efficacy of sphenopalatine ganglion block performed under general anesthesia in patients undergoing functional endoscopic sinus surgery (FESS) with operative blood loss and postoperative complications (headache, visual disturbances, nausea, vomiting, sore throat, swallow difficulty). Forty-five consenting patients were randomized to receive bilateral sphenopalatine ganglion block with saline (Group S, n = 15), bupivacaine 0.5% (Group B, n = 15), or levobupiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 13 publications
5
35
0
1
Order By: Relevance
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies associated the use of local agents, including lidocaine, with lower postoperative VAS scores and lower overall analgesic requirements in the postoperative period. Notably, several studies indicated decreased analgesic requirements extending beyond the length of action of these agents, with postoperative effects lasting throughout the 24‐hour postoperative period . The various agents that have been examined are further detailed in Supplementary Table ; importantly, 5 of 8 studies included contained level 1b evidence (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…reported that blood loss was significantly lower in patients who had SPGB through the posterior palatine canal route. Kesimci et al . evaluated the effect of SPGB in the control of nasal bleeding during endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the contrary, Kesimci et al reported that either bupivacaine or levobupivacaine provided effective postoperative analgesia after FESS. 21 The use of sympatholytic drugs (dexmedetomidine and clonidine) is proven for better hemodynamic stability. 22,23 The topical SPGB dates back to the previous century with the use of cocaine topical for minimal surgical procedures.…”
Section: Discussionmentioning
confidence: 99%